ANALISIS KEUANGAN TERHADAP DIVIDEN DAN NILAI PERUSAHAAN PADA PERBANKAN DOMESTIK KOMERSIAL MALAYSIA - Vidya Amalia Rismanty (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Loss of investor confidence means lost opportunity to develop, therefore increasing company value is the answer. This research aims to analyze the effect of profitability, liquidity, and solvability on dividend and its impact on company value. The population in this research as many as 8 companies listed in Bursa Malaysia period 2011-2015. By using saturated sampling method then 8 companies will be used as research sample. Eviews 9.0 statistical test is done by using regression test of panel data of random effect model. The research method used is quantitative descriptive by doing the activity of collecting secondary data from company annual report. The results showed that simultaneously, profitability/return on asset, liquidity/current ratio, and solvability/debt to equity ratio have significant effect on dividend/debt to equity ratio. Partially, profitability/return on asset and liquidity/current ratio variables significantly positive influence dividend/debt to equity ratio but solvability/debt to equity ratio have negative significant effect on dividend/debt to equity ratio. While dividend/debt to equity ratio has a significant positive effect on company value/price earning ratio